Challenging misrepresentations of black womanhood : media, literature and theory - Gammage, Marquita Marie, 1983-; Alameen-Shavers, Antwanisha (Anthem Press, 2019)
'Challenging Misrepresentations of Black Womanhood' investigates the stereotyping of Black womanhood and the larger sociological impact on Black women. The text details the historical and contemporary use of stereotypes against Black women and how Black women work to challenge and dispel false perceptions.
Keywords: African American women -- Social conditions.; African Americans in mass media.; Women in mass media.; African American women in literature.; African American women in popular culture.; Noires américaines -- Conditions sociales.; Noirs américains dans les médias.; Femmes dans les médias.; Noires américaines dans la culture populaire.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Women's Studies.; African American women in literature; African American women in popular culture; African American women -- Social conditions; African Americans in mass media; Women in mass media; Electronic book.